If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 3(2q + -7) Reorder the terms: 3 = 3(-7 + 2q) 3 = (-7 * 3 + 2q * 3) 3 = (-21 + 6q) Solving 3 = -21 + 6q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-6q' to each side of the equation. 3 + -6q = -21 + 6q + -6q Combine like terms: 6q + -6q = 0 3 + -6q = -21 + 0 3 + -6q = -21 Add '-3' to each side of the equation. 3 + -3 + -6q = -21 + -3 Combine like terms: 3 + -3 = 0 0 + -6q = -21 + -3 -6q = -21 + -3 Combine like terms: -21 + -3 = -24 -6q = -24 Divide each side by '-6'. q = 4 Simplifying q = 4
| (98x+27)9+5x-1=6(x+23) | | 9(2k+1)=-4+19k | | -3(-14q-19)-15q=-16-8+18q | | 6+5[1+2(2X-5)]=6(X-6) | | w/7+9=3 | | 4-2x=-2 | | 37=5x-13 | | 3+14f=6-9(-3f-17) | | 7(2u+11)=11u+17 | | -5(-6-6d)=6(20d+20) | | 8n-21=6n+5 | | -33z+28z^2-28=0 | | 3x=3(x+6) | | 1/4(4x+8)=6(x-3) | | -6(6-12s)=6(-2+8s) | | -42.12=7.8t | | 5c+12-6= | | -x^2+6x+14=0 | | -20u+12.03=-18.5u-15.27-5.4u | | 3x+2(x+5)=4(x+6) | | 10(6t+1)-15=t-(t+4) | | 121-5x=13x+19 | | x^3+2x^2-x=o | | -13v-16.08=1.76+9.22-10.8v | | 6x-4y+11=0 | | 6r^2-7r-5=5 | | -(15r+15)=3(-4r+1) | | -3(-4x+2)=5(x-3) | | 3(x+3)+3x=4(x+6)+1 | | x^4+72x-20=0 | | 8x+12=68 | | 2+g=14 |